La determinación presuntiva del sujeto pasivo acorde con el artículo 92 del Código Tributario y la necesidad de introducir reforma - Castillo Cofre, Gabriela Marylin (2016)
Currently the Ecuadorian System and Tax System has been running under government policies, and one of most significant aspects affecting the tax system is in practice the presumptive determination of taxpayer presumption that appears as a legal concept, with which the taxpayer claims not to have any other resource to prove your income and deductible expenses for tax payment, it not only erodes revenue itself, but deteriorating social and economic structure of a country. In addition to invalidating the pursuit of economic neutrality, it causes a misallocation of resources. For this reason the analysis and investigation of the effectiveness of this legislation becomes very important , because it produces negative the State effects , because the taxpayer is not limited and the law does not set prior to presumptively determine a tax liability sanction, therefore administration can not refuse to declare the presumption of liability, which comes when it is impossible to determine directly, why the documents supporting his statement is not acceptable for one primary or do not pay enough merit to accredit reason, so this determination shall be based on presumption of facts, evidence , circumstances that allow configuring the operative event and caused the amount of tax , or by applying coefficients determined by law . 6 By not setting the standard, the penalty may be issued to those who do not have the means for management to declare the existence of the tax liability , it is indirectly creating circumvention or decrease in the value of the tax liability , so the presumption is a term that is deduced by logic judgment or opinion, and to boast of assumptions made , are not guaranteeing the obligation of taxpayers or taxpayers filing their accounts and records and documents should contribute to the State to payment of taxes. Within this perspective particularly I establish the significance of the analysis of tax obligations with the clear characteristics of the presumptive determination to establish more effective mechanisms and improve tax collection. Among conventional forms of noncompliance with tax obligations, they are causing taxpayers to withhold payment because of taxes , creating tax avoidance , which is to modify their behavior so as to reduce or eliminate your debt, consequences they generate are a great loss of revenue for the state and thus the resources allocated will be shrinking , and thus the neglect of social needs . Any tax liability has the main object tribute satisfaction, determining the amount of the benefit ; so taxpayers must make the respective statements of expenses, providing evidence to support them , and generally meet a series of formal duties called by the Tax Code .